A modelling study for moisture diffusivities and moisture transfer coefficients in drying of solid objects - Dincer, Ibrahim; Dost, Sadik (International journal of energy research, 1996)
This article presents an effective analytical model for determining the moisture diffusivities and moisture transfer coefficients for solid objects (namely, infinite slab, infinite cylinder, sphere; and also for irregularly shaped objects, by using a shape factor) subject to drying applications in a medium. The unsteady‐state moisture diffusion analysis is used on the basis of two important criteria: 0·1 <Bi < 100 and Bi > 100. The drying coefficients and lag factors were employed. The analytical models are then verified using available experimental data taken from the literature. The results show that the method presented here can be used to determine the moisture diffusion coefficients and moisture transfer coefficients for such solid objects in a simple and accurate manner for a variety of drying applications.